An Update on Root Lesion Nematode Species Infecting Cereal Crops in the Southwest of Western Australia - Rhys G. R. Copeland; Sadia Iqbal; Tefera T. Angessa; Sarah J. Collins; Michael G. K. Jones; John Fosu-Nyarko (Crops)
Root-lesion nematodes (Pratylenchus spp.) reduce the yield and quality of cereal crops in Australia. Eleven of the ~90 species characterised are present in Australia, with those determined as economic pests of broadacre agriculture costing an estimated AUD 250 million annually. Two species, P. curvicauda and P. quasitereoides, recently re-described, were isolated from fields located in the grainbelt of Western Australia, but little is known about their distribution in the region surveyed in this study. To investigate this and possible co-infestations with other Pratylenchus spp., we surveyed seven commercial wheat, barley, and oat farms near Katanning, Cancanning, Kenmare, Duranillin, Darkan, and a barley seed-bulk nursery near Manjimup, all in the southwest grainbelt of Western Australia. Morphological and molecular characterisation of Pratylenchus spp. extracted from soil and plant roots indicated all fields surveyed were infested. Both P. quasitereoides and P. curvicauda were present as single or mixed populations with P. penetrans and/or P. neglectus, although they were not found in the same field. Analyses of the D2–D3 sequences of the identified nematodes indicated that the species found in Australia were distinct, particularly P. quasitereoides and P. curvicauda. This work suggests P. curvicauda is likely to be present more widely in the WA grainbelt. Expanding molecular diagnostic testing for Pratylenchus species in the region to account for both nematodes is urgently needed so effective management can be implemented.